A trans-acting sRNA SaaS targeting hilD, cheA and csgA to inhibit biofilm formation of S. Enteritidis - Lyu, Chongyang; Hu, Haijing; Cai, Linlin; He, Shuwen; Xu, Xinglian; Zhou, Guanghong; Wang, Huhu (Journal of advanced research, 2025)
[Display omitted] •sRNA SaaS inhibits biofilm formation by interacting with target mRNA (hilD, cheA, and csgA).•The space morphological structure of biofilm in polystyrene microplates was firstly obtained by using CLSM.•Transcriptomics and proteomics were applied to analysis the changes of gene expression and EPS component.•RNA-protein pull-down interactome datasets indicated that SaaS binds to Hfq uniquely among 193 candidate proteins. Salmonella Enteritidis has brought great harm to public health, animal production and food safety worldwide. The biofilm formed by Salmonella Enteritidis plays a critical role in microbial cross-contamination. Small non-coding RNAs (sRNAs) have been demonstrated to be responsible for regulating the formation of biofilm. The sRNA SaaS has been identified previously, that promotes pathogenicity by regulating invasion and virulence factors. However, whether the SaaS is implicated in regulating biofilm formation in abiotic surfaces remains unclear. This study aimed to clarify the effect of SaaS in Salmonella Enteritidis and explore the modulatory mechanism on the biofilm formation. Motility characteristics and total biomass of biofilm of test strains were investigated by the phenotypes in three soft agar plates and crystal violet staining in polystyrene microplates. Studies of microscopic structure and extracellular polymeric substances (EPS) of biofilm on solid surfaces were carried out using confocal laser scanning microscope (CLSM) and Raman spectra. Transcriptomics and proteomics were applied to analyze the changes of gene expression and EPS component. The RNA-protein pull-down and promoter–reporter β-galactosidase activity assays were employed to analyze RNA binding proteins and identify target mRNAs, respectively. SaaS inhibits biofilm formation by repressing the adhesion potential and the secretion of EPS components. Integration of transcriptomics and proteomics analysis revealed that SaaS strengthened the expression of the flagellar synthesis system and downregulated the expression of curli amyloid fibers. Furthermore, RNA-protein pull-down interactome datasets indicated that SaaS binds to Hfq (an RNA molecular chaperone protein, known as a host factor for phage Qbeta RNA replication) uniquely among 193 candidate proteins, and promoter–reporter β-galactosidase activity assay confirmed target mRNAs including hilD, cheA, and csgA. SaaS inhibits the properties of bacterial mobility, perturbs the secretion of EPS, and contributes to the inhibition of biofilm formation by interacting with target mRNA (hilD, cheA, and csgA) through the Hfq-mediated pathway.